Contextualizing Islamic Marital Values in the Digital Age: A Study of Religious Education Among Indonesian Youth - Fitri Liza; Achmad Yani; Tri Gunawan; Wilnan Fatahillah (Tunjuk Ajar: Journal of Education and Culture, 2025)
This study explores the interpretation of Fiqh al-Munākaḥāt by students of State Islamic Senior High Schools (Madrasah Aliyah Negeri) as a form of early sex education in the digital era, along with its implications for contemporary Islamic jurisprudence. Using a qualitative approach, data were collected from 112 students in Buleleng and Jakarta through online questionnaires and document analysis. Data analysis was conducted in three stages: reconciliation, presentation of patterns, and meaning construction. The theoretical framework integrates Habermas’s post-secular theory, Badran’s Islamic gender discourse, and Campbell’s concept of digital religion. The findings show that 78.6% of respondents acknowledge the significant influence of digital media on their understanding of Islamic marriage norms, while 61.6% find technology helpful in understanding related legal concepts. The integration of post-secular perspectives reveals religion’s relevance in modern public spaces. Islamic gender discourse provides insights into the evolution of gender roles among Muslim youth, while digital religion explains how religious authority and moral reasoning are mediated by online platforms in marital matters. This study introduces ‘digital fiqh’ as a new academic concept that reconceptualizes the understanding and practice of Islamic law within digitally-mediated religious spaces. Further research is recommended through longitudinal and comparative studies to understand the long-term impact of digitalization and to develop the framework of digital fiqh in contemporary Islamic legal studies.